ICBR-Diff: an Impairment Constraint Based Routing Strategy with Quality of Signal Differentiation - Amornrat Jirattigalachote; Paolo Monti; Lena Wosinska; Kostas Katrinis; Anna Tzanakaki (My University, 2010)
Latest advances in Wavelength DivisionMultiplexing (WDM) technology make it possible to build all-optical transparent networks, which are considered to be able to satisfy the rapidly growing capacity demand.However, in a transparent WDM network the optical signal transmitted from a source to a destination node might be degraded due to physical layer impairments induced by transmission through optical fibers and components.Several Impairment Constraint Based Routing (ICBR) algorithms have been proposed to consider physical layer impairments during the connection-provisioning phase in order to prevent selecting a lightpath with poor signal quality.However, these algorithms support only a single quality of transmission threshold for all connection requests, while next generation networks and the future Internet are expected to support a variety of services with potentially disparate QoS requirements.In this paper, we propose the use of bit error rate (BER) as a differentiation of service parameter for connection requests in optical WDM networks.This is achieved through the use of ICBR, whereby various BER thresholds are set depending on the QoS requirements for accepting/blocking the connection requests during the connection-provisioning phase.The evaluation results reveal that significant network performance improvement in terms of connection blocking can be achieved, compared to non-differentiated conventional routing and wavelength assignment (RWA) and ICBR algorithms.
Keywords: SIGNAL (programming language); Advanced Optical Network Technologies